Os efeitos do tempo de exposição do sujeito às atividades sem reforço programado sobre a efetividade do desempenho em esquema temporal de reforçamento - Aureliano, Lívia Ferreira Godinho (2008)
This study investigated the effects of duration exposure to activities without programmed reinforcers on performance under a temporal schedule of reinforcement. Two other questions guided this study: (a) Are there any changes in the patterns of activities that occur without programmed reinforcers dependent on the duration of exposure to these activities? (b) What would be the effect of the duration of this exposure over responding under a DRL schedule of reinforcement when subjects are placed in a standard operant chamber without access to other activities? Subjects were 4 male food deprived rats and 2 chambers were used: a standard operant chamber (1 compartment with lever and food recipient) and a 7 compartment chamber (activity chamber) in which subjects could engage on different activities: as bar pressing, eating, drinking, wood-chewing, and running. Bar presses were reinforced with food according to a DRL schedule that varied from 5 to 10 to 21s, but 2 subjects were exposed to this schedule on the standard chamber and the others on the activity chamber. Experimental sessions lasted 2 hours and bar presses, reinforce deliveries, and compartments visited were recorded. Results indicated performances in teach environment when DRL 10s or higher was in effect. On DRL 10s response and reinforcer rates and percentage of reinforced responses were higher, and time between reinforcements was lower for subjects on the standard chamber. In DRL 21s, however, these measures were reversed, suggesting that the availability of other activities could facilitate the acquisition and maintenance of performance on higher values DRL. There was indication of an increase on the percentage of reinforced bar pressing responses as a function of time of exposure to the experimental contingency in each session for all subjects. There were no significant differences on the percentages of reinforced responses of subjects on the standard or activity chamber box as a function of successive experimental sessions. However, percentages of reinforced responses were lower for subjects in the standard chamber at the beginning of the first sessions on each DRL value. Sequences of compartment visits, that seemed to be patterns were identified and the beginning of this patterns coincided with the increased effectiveness of the bar pressing responses. Results are discussed taking into account the differences between the criteria used in studies reported on the literature. The possible roles of the activities on the performance submitted on DRL schedules are also discussed